A New Host Plant of Red Pierrot Talicada nyseus Guerin, 1843 Recorded in Mumbai, Maharashtra, India - Fernandes, Jennifer Francis (Journal of the Bombay Natural History Society (JBNHS), 2016)
No Abstract.